(untitled) (Journal of Academic Research, 2025)
Background: Proximal humerus fractures are common in elderly patients. Locking plates offer stable fixation, but loss of reduction and varus deformity still occur, especially with poor medial support. Methods: 25 patients treated with PHILOS plates were studied. Calcar screws were used in some cases. Radiographs were assessed for neck-shaft angle and calcar screw position. Shoulder function was measured using the Oxford Shoulder Score. Results: 91% of optimally placed calcar screws were associated with neck-shaft angles between 130°–150°. Malposition rate was 32%. Fixation failure occurred in 3 patients without calcar screws; none occurred in the calcar screw group. Conclusion: Use of calcar screws and achieving a neck-shaft angle between 130°–150° reduces fixation failure. Proper placement improves medial support and patient outcomes.